Measuring Emotional Intelligence and the Productivity in a changing Information landscape: University of Guyana Library (Turkeyen Campus) - Harris, Clyden; Bacchus, Kezia (Advances in Social Sciences Research Journal, 2022)
The way in which information is disseminated within libraries has changed rapidly over the years. With technology playing a pivotal role in this change, an individual’s use of emotional intelligence within the workforce can boost the organization’s performance. As such, to promote increased productivity at the University of Guyana library, the aim of this research is to increase employees’ awareness of the use of emotional intelligence. A survey involving thirty-five (35) respondents were utilized to derive the researchers’ major findings. Questions from the survey were formulated with the help of the four pillars of emotional intelligence explored by Daniel Goleman. The four pillars of emotional intelligence are self-awareness; self-management; social awareness; and relationship management. The major findings from our research validates the researchers’ title and reflects that the level of Emotional Intelligence of library personnel was very high which resulted in a high productivity rate among the library personnel.